2020
DOI: 10.1136/archdischild-2020-319573
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam for convulsive status epilepticus in childhood: systematic review and meta-analysis

Abstract: ImportanceProlonged seizures are life-threatening emergencies associated with significant morbidity.ObjectiveTo determine the efficacy and safety of levetiracetam in treating convulsive status epilepticus (CSE) in childhood.Data sources and study selectionsPubMed, Embase, the Cochrane Central Register of Controlled Trials and Cumulative Index to Nursing and Allied Health Literature were searched from inception up to April 2020. Only randomised controlled trials (RCTs) that included children aged 1 month–18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Their pooled data also showed that there was no statistically significant difference in seizure termination rates or time to seizure termination in the two groups. A sub-analysis mirrored the earlier, 2020 meta-analysis 46 in that statistically more patients treated with fosphenytoin compared to levetiracetam experienced adverse drug events, respiratory depression and acute hypotension and also required more assisted respiratory support (p = 0.002). These differences were not seen in the levetiracetam and phenytoin comparison (p = 0.06).…”
Section: Current Managementmentioning
confidence: 66%
See 2 more Smart Citations
“…Their pooled data also showed that there was no statistically significant difference in seizure termination rates or time to seizure termination in the two groups. A sub-analysis mirrored the earlier, 2020 meta-analysis 46 in that statistically more patients treated with fosphenytoin compared to levetiracetam experienced adverse drug events, respiratory depression and acute hypotension and also required more assisted respiratory support (p = 0.002). These differences were not seen in the levetiracetam and phenytoin comparison (p = 0.06).…”
Section: Current Managementmentioning
confidence: 66%
“…44 An earlier meta-analysis suggested that sodium valproate was being increasingly used in the management of CSE, particularly in adults, despite the lack of good efficacy and safety data. 45 A systematic review and meta-analysis by Abdelgadir et al in 2020 46 and also by Feng et al in 2021 47 both concluded that levetiracetam is comparable to phenytoin (or fosphenytoin) but has the advantage of being superior in safety outcomes. Abdelgadir et al 46 included only RCTs, which comprised of 10 studies involving 1907 children.…”
Section: Sodium Valproatementioning
confidence: 99%
See 1 more Smart Citation